Operational efficiency and sustainability of vector control of malaria and dengue: descriptive case studies from the Philippines - van den Berg Henk; Velayudhan Raman; Ebol Antonietta; Catbagan Ben HG; Turingan Romulo; Tuso Marisol; Hii Jeffrey (Malaria Journal, 2012)
Abstract Background Analysis is lacking on the management of vector control systems in disease-endemic countries with respect to the efficiency and sustainability of operations. Methods Three locations were selected, at the scale of province, municipality and barangay (i.e. village). Data on disease incidence, programme activities, and programme management were collected on-site through meetings and focus group discussions. Results Adaptation of disease control strategies to the epidemiological situation per barangay, through micro-stratification, brings gains in efficiency, but should be accompanied by further capacity building on local situational analysis for better selection and targeting of vector control interventions within the barangay. An integrated approach to vector control, aiming to improve the rational use of resources, was evident with a multi-disease strategy for detection and response, and by the use of combinations of vector control methods. Collaboration within the health sector was apparent from the involvement of barangay health workers, re-orientation of job descriptions and the creation of a disease surveillance unit. The engagement of barangay leaders and use of existing community structures helped mobilize local resources and voluntary services for vector control. In one location, local authorities and the community were involved in the planning, implementation and evaluation of malaria control, which triggered local programme ownership. Conclusions Strategies that contributed to an improved efficiency and sustainability of vector control operations were: micro-stratification, integration of vector control within the health sector, a multi-disease approach, involvement of local authorities, and empowerment of communities. Capacity building on situational analysis and vector surveillance should be addressed through national policy and guidelines.